The Need Assessment and Academic Administration Model for Enhancing Elderly Care Based on the Concept of Caree-Oriented Education of Satri Wat Rakhang School - Tingaoum, Chalermraj (Journal of Dhamma for Life, 2026)
The objectives of this research were 1) to study the current state, the desirable state and needs assessment of a model of academic administration for elderly care based on the concept of career-oriented education of Satri Wat Rakhang school and 2) to develop a model of academic administration for elderly care based on the concept of career-oriented education of Satri Wat Rakhang school. This study was conducted with descriptive method. The population was Satri Wat Rakhang school and there were 95 informants, including deputy directors, assistant deputy directors, department heads, and teachers. The research instruments were the current state, the desirable state and needs assessment of a model of academic administration for elderly care based on the concept of career-oriented education of Satri Wat Rakhang school. The data were analyzed by frequency distribution, percentage, mean, standard deviation, mode, content analysis, and PNIModified Thailand’s transition into an aging society poses challenges not only for the government and the healthcare system but also for educational institutions, which play a crucial role in fostering knowledge, attitudes, and essential skills for sustainable and appropriate coexistence within an aging society. Therefore, this study sought to develop a practical and contextually appropriate academic administration model that responds to societal changes and can be feasibly implemented in a school setting. The proposed model aims to enhance students’ competencies, preparing them for future careers and enabling them to live with quality and dignity in an aging society.